2022
DOI: 10.1155/2022/5040461
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Comprehensive Nursing Intervention Under Internet-Based WeChat Platform Education on Postoperative Recovery of Puerperae Undergoing Cesarean Section

Abstract: Objective. To explore the effect of comprehensive nursing intervention under internet-based WeChat platform education on postoperative recovery of puerperae undergoing cesarean section (C-section). Methods. A total of 96 patients undergoing C-section in our hospital from June 2018 to October 2021 were selected for the retrospective analysis and grouped according to the nursing intervention modes as follows: patients who received a routine nursing intervention were included in the control group, and patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…e current multidisciplinary model of CHF is mainly implemented during the patient's hospitalisation, and it is difficult to organise a multidisciplinary team to provide comprehensive and individualised care and rehabilitation after the patient is discharged from the hospital [24][25][26]. With the popularity of smartphones, the WeChat platform as a new mobile media has its own advantages in the prevention and treatment of chronic diseases, such as large amount of information, wide coverage; wide range of users, rapid dissemination; peer-to-peer communication, personalized mutual assistance; and multimedia communication, low cost [10,27,28]. e WeChat platform is a good solution to the problem of inconsistency in time and place, and team members can communicate with each other and collaborate in multiple disciplines in the virtual network of WeChat [29].…”
Section: Discussionmentioning
confidence: 99%
“…e current multidisciplinary model of CHF is mainly implemented during the patient's hospitalisation, and it is difficult to organise a multidisciplinary team to provide comprehensive and individualised care and rehabilitation after the patient is discharged from the hospital [24][25][26]. With the popularity of smartphones, the WeChat platform as a new mobile media has its own advantages in the prevention and treatment of chronic diseases, such as large amount of information, wide coverage; wide range of users, rapid dissemination; peer-to-peer communication, personalized mutual assistance; and multimedia communication, low cost [10,27,28]. e WeChat platform is a good solution to the problem of inconsistency in time and place, and team members can communicate with each other and collaborate in multiple disciplines in the virtual network of WeChat [29].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Extended nursing based on the network interactive platform can effectively meet the needs of patients with diabetic kidney disease for functional training, diet, medication knowledge and other related diseases, and can enhance the self-management behavior of patients, so as to improve the self-efficacy and self-management behavior. [21][22][23] The research results of Zhou Shenghuo et al 24 showed that the extended nursing of the network had a good effect on the nursing of patients and reduced the occurrence of complications. In this study, the nursing effect of the study group was higher than that of the control group, and the incidence of adverse reactions in the control group and the study group was 20% and 7.5%, respectively, that is, the study group was lower than the control group.…”
Section: Discussionmentioning
confidence: 99%